Carbon nanowires reinforced porous SiO2/3Al2O3·2SiO2 ceramics with tunable electromagnetic absorption properties. Issue 9 (15th June 2019) - Dong, Yongpeng; Yin, Xiaowei; Wei, Hanjun; Li, Minghang; Hou, Zexin; Xu, Hailong; Cheng, Laifei; Zhang, Litong
Abstract: Porous SiO2 /3Al2 O3 ·2SiO2 ceramics decorated with carbon nanowires (CNWs) were manufactured by catalytic chemical vapor deposition (CCVD) for wide absorption band and high absorption application. The results show that the as-prepared CNWs grow uniformly in porous SiO2 /3Al2 O3 ·2SiO2 ceramics to form the three dimensional(3D) structure. The content of CNWs can be effectively controlled by changing the weight of catalyst, and the dielectric properties of CNWs-SiO2 /3Al2 O3 ·2SiO2 composite ceramics can be tuned. As expected, the CNWs-SiO2 /3Al2 O3 ·2SiO2 composite ceramics possess wonderful electromagnetic (EM) absorption properties due to the effects of conductive loss, impedance match and dipoles polarization. It can be concluded that the minimum reflection coefficient (RCmin ) of CNWs-SiO2 /3Al2 O3 ·2SiO2 composite ceramics reaches −31 dB at 9.1 GHz (which means 99.9% of EM wave powers are absorbed) and the effective absorption bandwidth (EAB) covers the whole X-band (8.2–12.4 GHz) at the thickness of 5.0 mm.